Family Counseling to Improve Attachment between Parents and Children - Yusuf, Nur Mawakhira; Masri, Subekti; Kasmi, Kasmi; Saldin, Muh; Rantekata, Nurul Ahwat; Ali, Salmiati S; Chaer, Ummul; Gunther Dress (Journal Of Human And Education (JAHE), 2024)
This community service is motivated by the significance of family counseling to improve attachment between parents and children.The purpose of this community service is that parents can establish attachment with their children through family counseling that has been programmed.The approach used in this community service activity is community education in the form of counseling and consultation activities with the door to door method which is carried out by interviewing family members and observing the interaction of family members while at the service location. The results of community service show that the attachment between parents and children is closely related to the ability of parents to provide attention, free time and support to meet the needs of children's physical and psychological needs. Family counseling is expected so that each member is able to carry out their duties and responsibilities properly, carry out the obligations of roles and functions as family members and create harmonious family relationships.